Prosthetic Reconstruction of Orbital Defects - Vincent, Aurora; Kohlert, Scott; Kadakia, Sameep; Sawhney, Raja; Ducic, Yadranko (Seminars in Plastic Surgery, 2019)
Orbital and craniomaxillofacial defects, in general, are best approached preoperatively by a multidisciplinary team with a clear reconstructive plan in place. Orbital defects result from a myriad of underlying diseases and injuries, and reconstruction after orbital evisceration, enucleation, or exenteration can pose a challenge to the reconstructive team. Reconstruction of orbital injuries with orbital implants and prostheses can lead to acceptable aesthetic outcomes, and the reconstructive surgeon should be familiar with current orbital implants and prostheses. Herein, the authors review terminology and classifications of orbital defects, different types of orbital implants, advantages and disadvantages of different orbital implant reconstructive options, types of orbital prostheses, and pros and cons of different prosthetic options.
Keywords: prosthetic; orbital implant; orbital defects